Productivity of different varieties of alfalfa in the south of the Rostov region - S. A. Ignatiev; T. V. Gryazeva; N. G. Ignatieva (Зерновое хозяйство России)
The work presents the assessment of productivity of such alfalfa varieties as ‘Rostovskaya 60’, ‘Rostovskaya 90’, ‘Lyutsiya’ and ‘Manycheskaya’ (of haymaking use) and ‘Kubanskaya zheltaya’ (of haymaking and grazing use). The varieties of haymaking use had a shorter period from the beginning of spring sprouting to the first mowing and seed ripening. In the first year the density of the alfalfa varieties was 300-340 plants per 1m2. At the end of the second year the density was 226-331 plants per 1m2 or 66.2% of the sown germinated seeds. At the end of the third year it was 171-248 plants per 1m2 or 38.0-49.6% of the sown germinated seeds. In the first year of use the density of the stand was significantly lower (912-1038 plants per 1m2) than in the second year (1116-1375 plants per 1m2). The density of the stand of the variety ‘Kubanskaya zheltaya’ was larger than that of the blue-hybrid varieties of alfalfa. During the second mowing the density of the stand was 221-331 plants per 1m2 and there was not any definite regularity in the amount of the stand of the blue-hybrid varieties of alfalfa. The density of the stand was determined by the productivity of green chop and dry matter. During the first mowing the productivity of the varieties was larger than during the second one. The alfalfa varieties showed high productivity during the second year of growing as well. The more productive blue-hybrid variety ‘Lyutsiya’ gave 24.1-27.4 t/ha of green chop and 5.2-8.4 t/ha of dry matter during the first mowing in the first year. During the second year its green chop productivity was 25.9-34.1 t/ha and its dry matter productivity was 6.4-8.6 t/ha. During all years the variety ‘Lyutsiya’ produced 28.5 t/ha of green chop and 7.4 t/ha of dry matter on average. It surpassed the variety ‘Rostovskaya 90’ on 0.8 t/ha of green chop and on 0.2 t/ha of dry matter, the variety ‘Rostovskaya 60’ on 1.5 t/ha of green chop and on 0.5 t/ha of dry matter, the variety ‘Manycheskaya’ on 3.1 t/ha of green chop and on 0.8 t/ha of dry matter. The variety ‘Kubanskaya zheltaya’ gave a larger yield (29.7 t/ha of green chop and 7.6 t/ha of dry matter) than the blue-hybrid varieties in one mowing. In sum, two mowings of the haymaking varieties gave a larger yield of green chop (41.8-45.7 t/ha) and dry matter (11.1-12.1 t/ha) than the variety ‘Kubanskaya zheltaya